Poverty in Guatemala - World Bank (Washington, DC, 2013)
This poverty assessment report has three main objectives: 1) to conduct an in-depth, multi- dimensional analysis of poverty building on the framework of the World Bank's World Development Report (WDR) for 2000/2001 using both quantitative and qualitative data; 2) to examine the impact of government policies and spending on the poor in key sectors; and 3) to use the empirical findings to identify options and priorities for poverty reduction in the future. Policy options are outlined not only in general, but for the specific themes and sectors covered. Chapter 2 examines the poverty "problem" using an array of monetary and social indicators, as well as perceptions of poverty identified by Guatemalan communities and households themselves. In general, poverty is determined by key household endowments and characteristics. These are analyzed in Chapter 3. Yet historical forces and contextual factors also play a crucial role in shaping patterns of poverty. These factors are discussed in Chapter 4. Chapter 5 examines the relationship between poverty and economic growth in Guatemala from a "macro" perspective. Chapter 6 builds on this macro-economic context to further examine the livelihoods and earnings opportunities of the poor at the household level ("micro" perspective), with a focus on rural livelihoods. The poor also rely on a portfolio of assets in order to forge opportunity, including education (Chapter 7), health (Chapter 8), basic utility services (Chapter 9), land and financial assets (Chapter 6), and access to transport (Chapter 10). Generally, the poor suffer from an unequal distribution of these assets. Chapter 11 provides an operational assessment of vulnerability, while Chapter 12 reviews existing social protection and social risk management mechanisms to assess their adequacy and offer insights into ways in which to strengthen them. As discussed in Chapter 4, one of the key remaining challenges for the Peace Agenda is the modernization of the state and a strengthening of community and social participation. Chapter 13 also considers the role of other important actors in development, namely the private sector, NGOs, and religious organizations. Finally, Chapter 14 builds on the empirical findings in the rest of the report to build an agenda for poverty reduction in Guatemala. Broadly speaking, a concerted strategy should be adopted to reduce poverty by building opportunities and assets, reducing vulnerability, improving institutions and empowering communities.